Collaborative Governance dalam Pengelolaan Kegiatan Ramadhan: Studi Kasus Malam 29 di Makam Sunan Ampel Surabaya - Lisa Indriati; Revalina Keisha Candra; Meilanny Adriana Selan; Izatul Rohma Oktavia; Naura Pramayssa Zahwara; Revienda Anita Fitrie; Galih Wahyu Pradana; Muhammad Farid Ma'ruf (Lembaga Pengembangan Kinerja Dosen, 2025)
Indonesia is one of the countries with the largest Muslim population in the world, has a very strong wealth of religious traditions. Religious activities that are often carried out by local tourists are pilgrimages to the tombs of saints, one of which is the Tomb of Sunan Ampel in Surabaya. On the 29th night of Ramadan, the area of ​​the Tomb of Sunan Ampel will experience a surge in visitors because it coincides with the last ten odd nights of the month of Ramadan. This study aims to determine the form of collaborative governance in the management of the 29th night of Ramadan activities at the Tomb of Sunan Ampel Surabaya. The main problem of the study is the process of collaboration between stakeholders in the management of complex and large-scale religious activities. The method used in this study is a descriptive qualitative method with interview, observation, and documentation techniques. The results of the study show that collaboration between parties in the management of Ramadan activities at the Tomb of Sunan Ampel is informal and only dominant in the Tomb of Sunan Ampel Foundation. Although there is functional cooperation, there is no written regulation to clearly regulate the division of roles. Therefore, efforts are needed to strengthen the structure and equal participation so that the governance of Ramadan activities can run more effectively and inclusively.